Perancangan Model Klasifikasi Metode Pemesanan Bahan Baku pada PT X - William Giovanno; I Gede Agus Widyadana (Jurnal Titra, 2022)
The activity of splitting purchase orders at the company is a quantity separation process that is carried out because there are requests for revision of needs and changes in the arrival schedule of raw materials. PO split activities have an inefficiency impact on procurement administration activities and warehousing activities. The company has designed several ordering methods that can accommodate these conditions, namely minimum order quantity, max lot size, and rounding value. Goal of the research is to create a classification model that categorize the optimal ordering method for raw materials. It begins by evaluating the pattern of raw material features, then designs the levels of the raw material's characteristic combination. The author then defines the scenarios that occur from the combination of characteristics and levels. Finally, by integrating raw material data to a defined scenario, the author creates an automated model. As a result of the research, the model could classify raw materials based on the company's characteristic data, determining whether or not the minimum order quantity, maximum lot size, and rounding value ordering method are required. Companies can use the categorization model to detect and classify raw material ordering methods more easily, rapidly, and consistently.